As competências gerenciais dos diretores de serviços administrativos das Faculdades de Tecnologia do núcleo regional de administração 10 - Arena, Beatriz (Universidade Federal de São Carlos, 2024)
This research aims to map the important managerial competences for directors of administrative services at the Faculties of Technology of the Regional Center for Administration 10 in carrying out their duties. Managing people based on competences, by valuing human participation in work processes, is an efficient way to improve the quality of services provided by the public sector and, in this process, public managers play a fundamental role, requiring recognition of managerial competences for the development of personnel that provides the best performance of professionals and an alignment of organizational strategies. This also applies to the directors of administrative services of the Technology Faculties of the Regional Administration Center 10 – administered by the Paula Souza Center. Therefore, proposing to deepen the understanding of the topic of managerial competences in the public sector, this research conducted a systematic review of the literature. To map managerial competences, a single case study with a mixed approach (quali-quantitative) was carried out. Data collection was carried out through documentary research, semi-structured interviews with a People Development project coordinator from the Human Resources Unit and an online questionnaire applied to 86% of the administrative services directors of the Regional Administration Center 10. results indicate that (i) the directors attributed a high degree of importance to all 28 competences of the theoretical models studied, with predominance of the competences of the rational goals and human relations models and the public interest factor; that (ii) the mapping of the institution's competences is the result of an interest in adapting to legislation, which made the process time-consuming, as it is conducted informally; and even though (iii) there are competences established only in the evaluation of institutional performance with a very particular configuration. This study contributed with guidelines for mapping the managerial competences of directors of administrative services at a higher education institution in which people management by competency is in its initial stage.
The managerial competences of the directors of administrative services of the Technology Faculties of the regional administration center 10
Keywords: Competências; Competências gerenciais; Setor público; Instituição de ensino superior; Competences; Managerial competences; Public sector; Higher education institution; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ADMINISTRACAO DE PESSOAL